Hybrid active slab with outer PCM Panels – Geothermal well to reduce the heat gain of a building roof - Mohammed F.Mohammed Ali; Yasser Abdel Latif; Rassol Hamed Rasheed; Ahmed Mohsin Alsayah; Angham Fadil Abed; Mohammed J. Alshukri; Karrar K.Abdul Hussein; Ahmed Al-Manea (International Journal of Thermofluids)
In hot climates, excessive heat gain through building roofs significantly increases cooling loads and energy consumption. This study aims to reduce roof heat gain by developing an innovative hybrid active slab with phase change material (PCM) panels and a geothermal well (HASP-GW). The HASP-GW system incorporates PCM panels and an active concrete slab embedded with water pipes as heat exchangers. Water at a constant temperature of 22 °C, sourced from a geothermal well, flows through these pipes to stabilize indoor temperatures. This research investigates the thermal performance of the HASP-GW with varying PCM transition temperatures and water flow rates using numerical simulations, validated against experimental results. The experimental setup involved two well-insulated test rooms (each 0.85 m × 0.85 m × 1 m); one equipped with the HASP-GW system and the other as a conventional comparison. Results showed that using the HASP-GW with a PCM transition temperature of 38–41 °C and a water flow rate of 1 L/min reduced the heat flux on inner surface of the roof, decrement factor, and inner surface temperature by 90.13 %, 0.127, and 16.24 °C, respectively, compared to a traditional roof. These findings indicate the potential of HASP-GW for energy-efficient roof cooling in hot climates.